2016
DOI: 10.1097/jce.0000000000000135
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support Procedure for Medical Equipment Maintenance Management

Abstract: Hospitals outsource several activities of the service support in order to focus on the core healthcare production as maintenance service. Recently, faced to the sophistication and the costs of medical equipment that continue to escalate, governments have implemented new reforms to control costs and improve the efficiency and the quality. Hospitals become interested in minimizing the total operational cost, by optimizing healthcare production planning and their support activities. Reorganizing the medical equip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The third and last module deals with the maintenance externalization decision, including the selection of an appropriate contracting policy for each externally maintained device. In developing countries, including the country in which the current study is conducted, there are generally four types of contracts to choose from (Masmoudi et al. , 2016): Type A*: Full package contract with all risks covered and all maintenance tasks, both corrective and preventive, performed by the subcontractor. Type A: It covers all TBM tasks, including both spare parts and labor. Type B: It involves the tasks related to either TBM, CBM or both of them combined and covers only the spare parts. Type C: It involves on-demand interventions, with neither spare parts nor labor costs covered under the contract.…”
Section: Development Of the Proposed Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The third and last module deals with the maintenance externalization decision, including the selection of an appropriate contracting policy for each externally maintained device. In developing countries, including the country in which the current study is conducted, there are generally four types of contracts to choose from (Masmoudi et al. , 2016): Type A*: Full package contract with all risks covered and all maintenance tasks, both corrective and preventive, performed by the subcontractor. Type A: It covers all TBM tasks, including both spare parts and labor. Type B: It involves the tasks related to either TBM, CBM or both of them combined and covers only the spare parts. Type C: It involves on-demand interventions, with neither spare parts nor labor costs covered under the contract.…”
Section: Development Of the Proposed Systemmentioning
confidence: 99%
“…The third and last module deals with the maintenance externalization decision, including the selection of an appropriate contracting policy for each externally maintained device. In developing countries, including the country in which the current study is conducted, there are generally four types of contracts to choose from (Masmoudi et al, 2016):…”
mentioning
confidence: 99%
“…They used the analytical hierarchy process (AHP) method consisting of six criteria (risk, equipment function, age, utilization, redundancy and mission criticality, recalls and maintenance requirements) and then suggested heuristic guidelines to select the appropriate maintenance strategy. The same heuristic reasoning was recently used by Masmoudi et al (2016) to decide the type of maintenance policy (outsourcing/in-house) and select the suitable service contract. They developed a criticality-based model with consideration of maintenance resources performance, risk and cost criteria.…”
Section: Medical Equipment Prioritization: Mcdm Approachmentioning
confidence: 99%
“…Equipment maintenance and repair is the most critical function which supports proper delivery of healthcare services. The WHO [11] observed that the biomedical engineers ought to optimize the best maintenance strategy to reduce the failure rate of medical equipment to improve the medical equipment reliability. The biomedical engineering sector has to ensure the safety of the equipment and the reduction of maintenance cost is paramount.…”
Section: Medical Equipment Maintenance Managementmentioning
confidence: 99%